Unveiling The Efficacy of Digital Pedagogy: Evaluating Online English Learning at High School Level - Hastini Abdul Gani; Mukrim Mukrim; Maghfira Maghfira; Oktaviani Oktaviani (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This research endeavors to explore the efficacy of online English learning at SMA Negeri 3 Palu. Its primary objective was to contribute to the ongoing discussion in this field by (1) investigating the effectiveness of online English language learning at SMAN 3 Palu and (2) identifying factors contributing to the challenges faced by both teachers and students in the context of online learning during the COVID-19 pandemic.. Employing a qualitative approach with a case study design, this study involved five English teachers and ten representatives from SMAN 3 students, with two students selected from each class taught by the teachers through purposive sampling. Data collection involved in-depth individual interviews with the informants. Thematic analysis techniques were applied, involving four stages: transcription, coding, categorization, and drawing conclusions from the coded data. The findings revealed that online English learning was ineffective for students at SMAN 3 Palu due to issues such as internet connectivity, the availability of students' smartphones, and the fact that the majority of students reside in remote areas of Sigi regency, which posed challenges for implementing online English learning.